2002
DOI: 10.1034/j.1399-3046.2002.02016.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient hyperphosphatasemia after organ transplantation in children

Abstract: Transient, isolated hyperphosphatasemia is a rare, benign condition of childhood. Few cases have been described in transplant patients. We report six cases: three after liver transplantation and three after kidney transplantation. Such a phenomenon was found to be as benign after organ transplantation as it is in healthy children. Hence, an isolated increase in the serum alkaline phosphatase level following transplantation should not be of concern in this population of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 18 publications
(18 reference statements)
2
14
0
1
Order By: Relevance
“…Fortunately, the clinical course of TH is usually time limited, as was observed in all our patients, in whom the S‐ALP returned to normal within four months after detection. This is in line with other reports on renal transplant patients in whom the spontaneous recovery was observed within three months except for one patient in whom the TH lasted for 204 days (Table 2) (10–12, 15). It seems therefore reasonable to limit the initial investigations to basic bone metabolism work‐up and await the evolution of the S‐ALP over 3–4 months before embarking on more sophisticated and invasive tests.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Fortunately, the clinical course of TH is usually time limited, as was observed in all our patients, in whom the S‐ALP returned to normal within four months after detection. This is in line with other reports on renal transplant patients in whom the spontaneous recovery was observed within three months except for one patient in whom the TH lasted for 204 days (Table 2) (10–12, 15). It seems therefore reasonable to limit the initial investigations to basic bone metabolism work‐up and await the evolution of the S‐ALP over 3–4 months before embarking on more sophisticated and invasive tests.…”
Section: Discussionsupporting
confidence: 92%
“…TH may also occur in patients post-solid organ Tx (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Similarly to the classic TH in nontransplanted children, the occurrence of TH in transplant recipients causes significant anxiety to the attending physician and raises similar questions -is there a need for a detailed work-up and when?…”
mentioning
confidence: 99%
“…None of the studies where increased urinary hydroxyproline was observed appear to have controlled for dietary collagen intake, which can influence urinary hydroxyproline levels (14). In addition, normal values of PTH have been reported in the following groups of children with THI: healthy ones (14,15), those with acute but mild illness (diarrhoea, respiratory tract infections) (15), and in patients after liver or kidney transplantation (16,17,18,19,20). Similarly, in our patients, the levels of OC, CTx, Ca, P and PTH were within normal ranges and not related to ALP dynamics, thus ruling out increased bone turnover.…”
Section: Discussionmentioning
confidence: 99%
“…None of these studies appears to have controlled for dietary collagen intake, which can influence urinary hydroxyproline levels 29. Among children who developed TH after liver or kidney transplantation, PTH levels were normal in 5 of 6 children,30 and normal urine hydroxyproline/creatinine ratio was reported in one 5 year old boy 31. In our study, the similar mean levels of calcium, magnesium, phosphorus and PTH across AP groups did not support increased bone resorption among children with TH.…”
Section: Discussionmentioning
confidence: 99%